2013
DOI: 10.1155/2013/924870
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Spin-Labeled 1-Ethyl-1-nitrosourea against Oxidative Stress in Liver Induced by Antitumor Drugs and Radiation

Abstract: This study was carried out to investigate possible protection effect of 1-ethyl-3-[4-(2,2,6,6-tetramethylpiperidine-1-oxyl)]-1-nitrosourea (SLENU), synthesized in our laboratory, against oxidative liver injuries induced in mice treated by antitumor drugs: doxorubicin (DOX), bleomycin (BLM), or gamma irradiation (R). Specifically, alterations in some biomarkers of oxidative stress, such as lipid peroxidation products measured as malondialdehyde (MDA) levels and activities of the antioxidant enzymes, superoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Combinations of SLENU and natural antioxidants reduce oxidative toxicity as compared to the same combinations of SLCNUgly. Our study confirms once again in vivo protective abilities of SLENU against oxidative toxicity of clinically used antitumor antibiotics and radiation 38,39 . Gadjeva and co-workers, 1994 40 using in vitro spintrapping EPR method demonstrated that SLENU possessed high superoxide radical scavenging activity (SSA) even higher than antioxidant Trolox.…”
Section: Discussionsupporting
confidence: 83%
“…Combinations of SLENU and natural antioxidants reduce oxidative toxicity as compared to the same combinations of SLCNUgly. Our study confirms once again in vivo protective abilities of SLENU against oxidative toxicity of clinically used antitumor antibiotics and radiation 38,39 . Gadjeva and co-workers, 1994 40 using in vitro spintrapping EPR method demonstrated that SLENU possessed high superoxide radical scavenging activity (SSA) even higher than antioxidant Trolox.…”
Section: Discussionsupporting
confidence: 83%
“…Using the EPR method we had shown that spin-labelled nitrosoureas could scavenge 2 O − ⋅ and thus exhibited high superoxide scavenging activity (SSA) [15]. Moreover, by our studies, we have demonstrated beneficial effects of SLENU, recently synthesized in our laboratory, on drug-induced oxidative toxicity in rat blood and in liver of mice [16]- [18].…”
Section: Introductionmentioning
confidence: 97%
“…In vitro was detected the synergistic effect of the spin-labeled nitrosourea 1-ethyl-3-[4-(2,2,6,6tetramethylpiperidine-1-oxyl)] -1-nitrosourea (SLENU) on the cytotoxicity of bleomycin and farmorubicin in human lymphoid leukemic tumor cells [21]. Recent studies have demonstrated the protective effect of SLENU against drug-induced oxidative stress in liver and blood in experimental animals [22,23].…”
mentioning
confidence: 99%